2008
DOI: 10.1111/j.1574-6976.2008.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and genetics ofShigellaO antigens

Abstract: This review covers the O antigens of the 46 serotypes of Shigella, but those of most Shigella flexneri are variants of one basic structure, leaving 34 Shigella distinct O antigens to review, together with their gene clusters. Several of the structures and gene clusters are reported for the first time and this is the first such group for which structures and DNA sequences have been determined for all O antigens. Shigella strains are in effect Escherichia coli with a specific mode of pathogenicity, and 18 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
283
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 283 publications
(293 citation statements)
references
References 159 publications
(153 reference statements)
6
283
0
4
Order By: Relevance
“…The comparison analysis in this study showed that Ͼ98% of the kmer ID results were concordant with the results derived by traditional methods. The isolates of S. flexneri belonging to ST1753, misidentified by TB&S as S. boydii due to a dysfunctional wzx [1][2][3][4][5] gene, highlight one of the problems with using serology to identify Shigella to the species level (15). Historically, S. boydii and S. dysenteriae were differentiated biochemically by the mannitol test, and the relationship between these two species within CC145 and CC288 demonstrates that separating species based on one test can be misleading with respect to their true phylogenetic relationship.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison analysis in this study showed that Ͼ98% of the kmer ID results were concordant with the results derived by traditional methods. The isolates of S. flexneri belonging to ST1753, misidentified by TB&S as S. boydii due to a dysfunctional wzx [1][2][3][4][5] gene, highlight one of the problems with using serology to identify Shigella to the species level (15). Historically, S. boydii and S. dysenteriae were differentiated biochemically by the mannitol test, and the relationship between these two species within CC145 and CC288 demonstrates that separating species based on one test can be misleading with respect to their true phylogenetic relationship.…”
Section: Resultsmentioning
confidence: 99%
“…With the exception of serotype 6 strains, all S. flexneri strains share a polysaccharide backbone composed of a linear tetrasaccharide, and the different serotypes arise as a result of glucosylation and/or O-acetylation of this polysaccharide backbone at various positions (8). S. boydii and S. dysenteriae share the same O antigen structure as that of E. coli, and the majority of isolates have a well-defined and limited set of O antigens (2). Using the traditional set of sugars, S. dysenteriae is generally the least reactive species of Shigella and is characterized by the inability to ferment mannitol (1).…”
mentioning
confidence: 99%
“…2A). A BLAST search demonstrated that each of these genomes contains the S. flexneri 6 O antigen (9), while all S. flexneri isolates from clade S5 contain the O13 antigen. The phylogeny demonstrates that genomes with the S. flexneri 6 O antigen are not closely related to sequenced S. flexneri genomes with the O13 antigen as determined on the basis of genomic content.…”
Section: Pan-genome Comparisons Betweenmentioning
confidence: 99%
“…Additionally, clinical symptoms often cannot differentiate Shigella infection from Escherichia coli infection or distinguish between Shigella species (8). Further confounding accurate identification, some O antigens present in Shigella are identical to those found in E. coli (9). Serotyping is the current gold standard method for Shigella species determination, but cross-reactivity among Shigella isolates, and E. coli isolates, may confound results (10).…”
mentioning
confidence: 99%
“…Recently, Iguchi (2015) reported antigenic relationships between E. coli O38 and S. dysenteriae 8; E. coli O169 and O183 with S. boydii 6 and 10. Although 21 shared O antigens were recognized between E. coli and Shigella (Iguchi, 2015), in the case of S. boydii 18 no antigenic cross-reaction was observed with any other E. coli or Shigella somatic antigen (Liu, 2008). Previously, our laboratory reported E. coli strains isolated from three geographic zones with antigens from S. boydii 16 showing characteristics of ETEC (Navarro, 2010).…”
Section: Discussion:-mentioning
confidence: 99%